2017
DOI: 10.18632/oncotarget.23809
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of protein arginine methyltransferase 6 expression in colon cancer

Abstract: Protein arginine methylation is involved in cellular differentiation and proliferation. Recently, aberrant expression of protein arginine methyltransferases, which are responsible for the methylation reaction, has been reported in various types of cancer. However, there is no clear evidence regarding the prognostic value of abnormal PRMT6 expression in colorectal cancer or the effect of PRMT6 regulation on CRC cells. We investigated the expression patterns of PRMT6 in patients with stage II and III CRC. We det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Observations from clinical samples showed that 75% of colorectal cancers had CARM1 overexpression [18]. In our recent study, patients with PRMT6-positive CRC by immunohistochemistry had shorter disease-free survival than those with PRMT6-negative CRC in both univariate and multivariate analyses [19]. All these studies strongly suggest that CRC tissues from patients might be suitable in vivo source for identification of arginine methylation.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Observations from clinical samples showed that 75% of colorectal cancers had CARM1 overexpression [18]. In our recent study, patients with PRMT6-positive CRC by immunohistochemistry had shorter disease-free survival than those with PRMT6-negative CRC in both univariate and multivariate analyses [19]. All these studies strongly suggest that CRC tissues from patients might be suitable in vivo source for identification of arginine methylation.…”
Section: Introductionmentioning
confidence: 80%
“…Based on the previous studies [16,18,19], we first examined the presence of three type I PRMTs, namely PRMT1, PRMT4 and PRMT6, by Western immunoblot using CRC tissue extracts from patients with stage II and III as well as DLD1 and HCT116 cell lysates. As shown in Fig.…”
Section: Expression Of Type I Prmts and Arginine Methylation Profilesmentioning
confidence: 99%
See 1 more Smart Citation
“…The p21 plays an important role in the development and progression of cancer, and hypermethylation of p21 leads to downregulation of p21 gene expression . Downregulated expression of PRMT6 in CRC cells can induce p21 overexpression and inhibit cell growth and colony formation capacity . PRMT6 is often found to be overexpressed in cancers, including CRC, bladder cancer, lung cancer, prostate cancer, and breast cancer .…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated expression of PRMT6 in CRC cells can induce p21 overexpression and inhibit cell growth and colony formation capacity . PRMT6 is often found to be overexpressed in cancers, including CRC, bladder cancer, lung cancer, prostate cancer, and breast cancer . In the present study, we found PRMT6 hypomethylation was significantly associated with CRC.…”
Section: Discussionmentioning
confidence: 99%